PENGARUH KESEIMBANGAN KERJA HIDUP PADA KOMITMEN ORGANISASIONAL DENGAN PERSEPSI TERHADAP KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI PEMODERASI - Elfitra Azliyanti; T. Hani Handoko (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2014)
Work life balance is a condition when a person can meet the needs and achieve a better balance of jobs and in the life outside of work , such as home life , social life with colleagues outside of work , health , leisure and spirit of the employees themselves . Employees are able to balance between areas of their lives on the job and off the job , the desire to remain in the organization is enhanced. Organizational commitment is often associated with employee perceptions of transformational leadership. Employees' perception of transformational leadership will increasingly make the employee's desire to remain in the organization is enhanced. Perceptions of transformational leadership will strengthen the influence of the work life balance on employee organizational commitment. This study aimed to examine the effect of work life balance in the organizational commitment of employees to the perception of transformational leadership as a moderating . The survey was conducted on 200 nurses Hospital in Jogjakarta . Questionnaires were collected 175 questionnaires , but only 165 questionnaires can be used . Data analysis using regression analysis moderasian . The results showed that the work life balance significant negative effect on affective and normative commitment to employees , but had no effect on employee commitment kontinuans . Perceptions of transformational leadership is not a moderating relationship work life balance on employee organizational commitment.